Comparative Analysis of Entrepreneurial Competencies Development among University Students - A. V. Pesha; M. N. Shavrovskaya; T. A. Lapina (Moscow Polytechnic University, 2023)
The article presents the results of an empirical study aimed at a comparative analysis of the level of students' entrepreneurial competencies of various forms of education (full-time, parttime, correspondence courses forms). The sample included 564 students of Ural State University of Economics (Yekaterinburg) and Omsk State University named after F.M. Dostoevsky (Omsk) of non-core areas of training. Empirical data were collected using an online survey and the method of narrative essays. The data obtained were interpreted and processed using qualitative and quantitative analysis methods, including descriptive statistics, correlation analysis (Pearson correlation coefficient, R), one-factor analysis of variance, factor analysis and qualitative analysis of student histories. The conducted research makes it possible to assess the differences in the level of assessed competencies of students depending on the form of study, to determine the correlation of the presence of entrepreneurial intentions and assessments of students' entrepreneurial competencies, as well as to analyze the attitude of students to the importance of the formation of entrepreneurial competencies at the university. As a result, statistically significant differences in the values of indicators of competence development by the factor of the education form by university students were revealed. Based on the data obtained on the research issues, the authors actualize the importance of attention to the development of entrepreneurial intentions and competencies of university students in non-core areas of training, including through the introduction of special disciplines into the curricula, which can become one of the predictors of the economic and social well-being of the country.